2016
DOI: 10.1186/s40712-016-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimization of MRR and surface roughness in wire electro discharge machining (WEDM) of D2 steel using Taguchi-based utility approach

Abstract: Background: This paper reports the effect of process parameters on material removal rate (MRR) and surface roughness (Ra) in wire electro discharge machining of AISI D2 steel. Findings: The wire electro discharge machining characteristics of AISI D2 steel have been investigated using an orthogonal array of design. The pulse on time and servo voltage are the most significant parameter affecting MRR and surface roughness during WEDM process. The simultaneous performance characteristics MRR and surface roughness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 24 publications
2
20
0
2
Order By: Relevance
“…Abbasi et al [13] developed a mathematical model during machining HSLA steel of 38 HRC in WEDM process considering voltage, current, pulse on-time and wire speed and found that, the effect of pulse on-time is greater for SR trailed by wire speed, power and pulse. Manjaiah et al [14] examined the WEDM characteristics of tool steel D2 using OA design and identified that, servo voltage and pulse on-time are the utmost important parameter that affects SR and MRR through utility approach and found that, machined surface hardness value is greater than the unmachined surface because of frequent quenching effect and the surface containing different oxides due to the formation of recast layer.…”
Section: Fig 1wedm Process [9]mentioning
confidence: 99%
“…Abbasi et al [13] developed a mathematical model during machining HSLA steel of 38 HRC in WEDM process considering voltage, current, pulse on-time and wire speed and found that, the effect of pulse on-time is greater for SR trailed by wire speed, power and pulse. Manjaiah et al [14] examined the WEDM characteristics of tool steel D2 using OA design and identified that, servo voltage and pulse on-time are the utmost important parameter that affects SR and MRR through utility approach and found that, machined surface hardness value is greater than the unmachined surface because of frequent quenching effect and the surface containing different oxides due to the formation of recast layer.…”
Section: Fig 1wedm Process [9]mentioning
confidence: 99%
“…Thiagarajan et al [6] reported the combined influence of machining variables like pulse on duration (P on ), pulse off time (P off ), wire feed (WF) and wire tension (WT) at the MRR and SR in electric discharge machining of AISI D3 steel. A detailed study as multi-objective optimization was made by Manajaiah et al [7] for AISI D2 steel in WEDM and inferred that the MRR, SR and recast layer thickness (RLT) are found in direct proportion with P on . Ikram et al [8] carried an insight investigation in WEDM of AISI D2 steel.…”
Section: Introductionmentioning
confidence: 99%
“…The author concluded that pulse on time, pulse off time, peak current and spark voltage had higher impact on surface roughness [9]. Manjaia et al [10] statistically optimized the pulse on time, pulse off time, servo voltage and wire feed for WEDM of AISI D2 tool steel for the response of MRR and SR. The author resulted the higher significance of pulse on time and servo voltage on performance parameters [10].…”
Section: Introductionmentioning
confidence: 99%